ETNOSAINS DALAM PEMBUATAN PERAHU TRADISIONAL MASYARAKAT BATANGHARI: POTENSI DAN IMPLEMENTASINYA DALAM PEMBELAJARAN IPA BERBASIS KEARIFAN LOKAL - Novi Ramayani; Bambang Hariyadi; Tedjo Sukmono; Revis Asra; Muhammad Haris Effendi HSB (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The traditional boat making by the Batanghari community in Jambi is a cultural heritage containing ethnoscience values. This local knowledge encompasses several aspects, including physics, biology, and technology, which can be integrated into science education in schools. This article discusses the potential of ethnoscience in traditional Batanghari boat making and its implementation in science learning based on local wisdom. The aim of this research is to explore and analyze the local wisdom of the community along the Batanghari River as a natural science learning resource. This study is a qualitative descriptive research. The subjects of this research are boat-making experts and community leaders, with the research object covering the area along the Batanghari River. The technique used is snowball sampling with instruments including observation sheets, interview sheets, and documentation. The data analysis technique applied is the Miles and Huberman model (data reduction, data display, and conclusion drawing/verification). The results of this research show that the local wisdom of the communities along the Batanghari River has a significant potential to be used as a science learning resource. This local wisdom has been formed over generations, influencing the daily cultural patterns and community activities, which can effectively bridge indigenous knowledge with formal science concepts in school.